Otoritarianisme Pemahaman Keagamaan: Melacak Akar Kekerasan terhadap Perempuan dalam Rumah Tangga - Juliansyahzen, Muhammad Iqbal (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
The phenomenon of violence against women in Indonesia is always increasing and leaves a devastating impact on various fronts. Every woman with various backgrounds has the same vulnerability to become a victim. The causes of violence against women are as diverse as patriarchal culture, labeling of women with weak physical conditions, to gender-biased interpretation of religious texts. The practice of religious interpretation which tends to position the text as a rigid and final entity is certainly not relevant to the spirit of Islam in realizing general prosperity, especially between men and wives. The text is also seen as justification for personal interests and even groups. This imbalance then gives birth to what is called authoritarianism. The practice of religious authoritarianism eventually raises the problem of injustice and even violence that often makes women or wives victims. In religious discourse, historically the root of violence in originated from the paradigm of human creation. Women are considered as complementary or subordinate creatures of men. This understanding is based on religious texts such as QS An-Nisa [4]: ​​34 which is commonly understood as a form of giving the mandate of male authority over women. Therefore, insight into authoritative interpretation is needed. Religious texts are not final entities, but always intersect with social and cultural realities.Equality, authority, Religious authoritarianism